2017
DOI: 10.1177/1756287217697662
|View full text |Cite
|
Sign up to set email alerts
|

Bovine serum albumin–glutaraldehyde (BioGlue®) tissue adhesive versus standard renorrhaphy following renal mass enucleation: a retrospective comparison

Abstract: Background: To present the operative and post-operative comparison between patients who underwent tumor-bed closure with sutures compared with bovine serum albuminglutaraldehyde (BioGlue ® ) tissue sealant only. Methods: We retrospectively analyzed data from our ongoing database of 507 eligible patients who underwent open NSS nephron-sparing surgery in our department between January 1995 and May 2014. Patients had tumor-bed closure with sealant adhesive (255 patients) or standard suture technique (252 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 18 publications
0
28
0
Order By: Relevance
“…Second, although not statistically significant on multivariate analysis, the use of the tissue adhesive (BioGlue R ) instead of sutures was shown to play a protective role against AKI on univariate analysis. This could be attributed to the advantages of using tissue adhesive including shorter ischemia time and less viable tissue loss during tumor bed closure, as we showed in a previous study [20].…”
Section: Discussionmentioning
confidence: 52%
“…Second, although not statistically significant on multivariate analysis, the use of the tissue adhesive (BioGlue R ) instead of sutures was shown to play a protective role against AKI on univariate analysis. This could be attributed to the advantages of using tissue adhesive including shorter ischemia time and less viable tissue loss during tumor bed closure, as we showed in a previous study [20].…”
Section: Discussionmentioning
confidence: 52%
“…Bioreactors will add a significant volume (50-2000 L) HSA extracted from the crew could have some other beneficial applications besides habitat construction. BSA is currently employed as a tissue adhesive, [64] so it is likely that HSA could be employed in an analogous manor. HSA could also be re-introduced into crew members via intravenous (IV) therapy to treat a variety of clinical conditions, including restoration of blood volume, treatment of shock, acute burns and other conditions associated with hypervolemia.…”
Section: Discussionmentioning
confidence: 99%
“…53 Renorrhaphy techniques using tissue adhesive sealant have also been described and have demonstrated favorable reductions in warm ischemia time and blood loss with use of bovine serum albumin-glutaraldehyde (BioGlue ® , CryoLife, Inc, Kennesaw, GA, USA). 54 A subsequent study assessing renal function via DMSA scan among patients undergoing PN revealed decreased volume loss by approximately 50% with use of the tissue adhesive compared with standard suture renorrhaphy. 55 Takagi and colleagues compared monopolar coagulation of hemorrhagic areas and a tissue-sealing sheet (TachoSil ® , Baxter Healthcare, Deerfield, IL, USA) versus standard renorrhaphy.…”
Section: Renorrhaphymentioning
confidence: 99%